Efeito de quitosana e extratos fenólicos de subprodutos do processamento de acerola e jabuticaba no controle da podridão causada por Lasiodiplodia spp. em mamão - Gomes, Ana Cristina Alves (2020)
Stem-end rot caused by species of Lasiodiplodia is one of the main diseases that cause postharvest losses in papaya fruits. One of the control methods of Lasiodiplodia spp. it is the use of synthetic fungicides, however these have not been totally effective in the control and cause negative impacts on human health and the environment. With this, the importance of the search for new technologies for the control of stem-end rot in papaya fruits arises. Chitosan is a biopolymer with antimicrobial properties, low toxicity and the ability to form gel, which allows its use on coating of fruits. The incorporation of natural antimicrobial compounds, such as phenolic compounds, in coatings can be an alternative to control stem-end rot in papaya fruits. This work aimed to evaluate the effect of chitosan and phenolic extracts of the by-products of the processing of acerola and jabuticaba in the control of rot caused by different species of Lasiodiplodia (L. theobromae, L. pseudotheobromae, L. euphorbicola, L. viticola, L. hormozganensis) on papaya. For this, analyzes of the identification of the components of the phenolic extracts of the by-products of the processing of acerola and jabuticaba were carried out, as well as the in vitro action alone and in combination of these extracts and chitosan on the radial mycelial growth of Lasiodiplodia species. In situ tests were carried out to evaluate the effect of coatings formulated with chitosan and phenolic extracts on the severity of rot caused by Lasiodiplodia spp. on papaya fruits. Physico-chemical analyzes (color, loss of fresh weight, firmness, pH, titratable acidity, and soluble solids) were performed to evaluate the effects of coatings on the postharvest quality of the fruits. Twenty-six different phenolic compounds were identified, with flavonoids being the major group present in the tested extracts. Chitosan (3, 4 and 5 mg/mL) and extracts of acerola (75 and 100 mg/mL) and jabuticaba (50, 75 and 100 mg/mL) inhibited mycelial growth in all isolates of Lasiodiplodia. The combined application of different concentrations of chitosan (3 or 4 mg / mL) and extracts of acerola (50 or 75 mg/mL) or jabuticaba (75 or 100 mg/mL) showed additive interactions in the inhibition of fungal isolates. The application of coatings of chitosan (4 mg/mL) and extracts of acerola (50 or 75 mg / mL) or jabuticaba (75 or 100 mg/mL) delayed the development of rot in papaya artificially infected with Lasiodiplodia isolates for 8 days storage at room temperature (25 ± 1 ° C). Coatings with 4 mg / mL of chitosan and 75 mg/mL of acerola extract or 100 mg/mL of jabuticaba extract were the most effective in controlling the development of rot in papaya fruits, regardless of the species of Lasiodiplodia tested. The coatings with chitosan (4 mg/mL) and acerola extract (75 mg/mL) or jabuticaba extract (100 mg/mL) did not negatively affect the physicochemical parameters indicative of the postharvest quality of papaya fruits during the storage. These results indicate that coatings formulated with additive concentrations of chitosan and phenolic extracts of acerola or jabuticaba may be new strategies for the control of post-harvest rot caused by Lasiodiplodia in papaya fruits.